2011
DOI: 10.3989/gya.022810
|View full text |Cite
|
Sign up to set email alerts
|

A simple model of the diffusion phenomena taking place during the debittering process of green table olives

Abstract: RESUMENUn modelo simple del fenómeno de difusión que tiene lugar durante el proceso de desamarizado de aceitunas verdes de mesa.Se ha cuantificado el cambio en la concentración de sodio y calcio en la pulpa y en la lejía durante el tratamiento alcalino de aceitunas. La concentración promedio de sodio en la pulpa aumentó de 0,0045 a 0,395 meq Na/g mientras que la de calcio creció de 0,018 a 0,0252 meq Ca/g. La textura de las aceitunas disminuyó casi linealmente de 375 gf a 235 gf durante el tratamiento alcalino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…This could be due to the resistance and barrier to diffusion of sucrose and lactitol molecules offered by the skin of cherries. A similar finding was described by Maldonado et al [26,27,31] where the difference in diffusivity could be due to a more impermeable structure in fruit skin (natural barrier) against the diffusion of compounds.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…This could be due to the resistance and barrier to diffusion of sucrose and lactitol molecules offered by the skin of cherries. A similar finding was described by Maldonado et al [26,27,31] where the difference in diffusivity could be due to a more impermeable structure in fruit skin (natural barrier) against the diffusion of compounds.…”
Section: Resultssupporting
confidence: 84%
“…This characteristic of the epidermis, in addition the cuticle layer, which covers fruits such as cherries and others, present a barrier effect to the diffusion of substances through it and is different from the diffusion in the mesocarp. Maldonado et al [31] and Zuritz and Maldonado [25] found this when studying sodium diffusivity in olives.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Permeation of NaOH is a function of the treatment conditions such as lye concentration and temperature, along with olive variety and maturity (Maldonado et al, 2011). UAD increased penetration rate of sodium hydroxide solution in comparison with CD, significantly (Fig.…”
Section: Penetration Rate Of Sodium Hydroxide Solutionmentioning
confidence: 97%